CALCULATION OF BULK VISCOSITY OF TWO-COMPONENT FLUIDS FROM SECH(AT) FORM OF THE TIME CORRELATION FUNCTION - Ali Hossein Mohammand Zaheri
To study transport coefficient of one component of classical dense fluids a considerable amount of work has been done during last three decades. Extensive molecular dynamics (MD) stimulation [1] studies for hard sphere fluids and Lennard-Jones (LJ) fluids have been undertaken, during this period, to find out the transport properties. But, the transport coefficient in two-component fluids are least understood. All among the transport coefficients the bulk viscosity of fluids which has relevance to the behavior of fluids under rapid loading conditions. In other words, the bulk viscosity can be considered as a measure of the resistance offered by a medium subjected to the forces of compression or expansion. It also plays an important role in the study of the dynamical structure factor.
Keywords: Physics; Materials science